Cyber- counseling: is it really new? - Zainudin, Zaida Nor; Mohamad Yusop, Yusni (Malaysia Association of Research and Education for Educators, 2018)
This is a conceptual review paper to evaluate the effects of the revolution of cyber-counseling. The study reviews literature on the history of computer using in counselling services as early as the 1960s, the evolution and relovution of using the computer in providing counselling services. Studies and surveys were analysed and lay out chorologically the evolution of cybercounseling based on the years. The paper also analyses two historical eras, the history of computer usage in counselling and the history of internet usage in counselling. The findings of the paper also identified softwares created and used, followed by how the counsellors practising the counselling using computer and internet. Conclusions from the literature are drawn that cyber-counseling seems new but it is actually has been practising decades ago. The paper ends with recommendation on future research.